Review: Physical activity interventions for the mental health and well‐being of adolescents – a systematic review. Issue 4 (9th June 2021) - Hale, Gabrielle E.; Colquhoun, Luke; Lancastle, Deborah; Lewis, Nicky; Tyson, Philip J.
Abstract : Background: Rates of physical activity decline throughout adolescence, and evidence indicates that this has an adverse impact on psychological health. This paper aims to synthesise available evidence for physical activity interventions on the mental health and well‐being of young people (11–19 years) from the general population. Method: Nine databases were searched to identify studies published between January 2005 and June 2020: Web of Science, ProQuest Psychology Journals, PsycINFO, Pub Med, ASSIA, CINHAL PLUS, SPORTDiscus, EMBASE and Wiley Online Library. Key search terms included 'physical activity intervention', 'mental health' and 'adolescen*'. Eligible studies were independently screened by two authors based on inclusion/exclusion criteria. Results: Twenty‐eight interventions were narratively synthesised in four categories: Quality of Life (QOL), self‐esteem, psychological well‐being and psychological ill‐being (e.g. depression, stress). A large proportion (67.9%) of interventions were multicomponent and combined physical activity with other features such as health education (e.g. nutrition). However, only a limited number ( N  = 5) specifically addressed mental health. Findings suggest that interventions are useful in improving psychological well‐being and QOL, yet evidence for self‐esteem is mixed. Conclusions: Although effectiveness in improving well‐being is evident, evidence for a reduction in the frequency and severity of mental health problems is less clear. A summary of the overall impact of physical activity interventions on the mental health of young people is presented.